Exploring ethnic differences in student engagement and assessment preferences in higher education - Pauldy Otermans; Sofia Barbosa Boucas; Laiba Nasar; Stephanie Baines (Journal of Learning Development in Higher Education)
This study examined the relationship between student engagement, assessment preferences and ethnicity among university students. 64 participants who were enrolled in either BSc Psychology or BSc Psychology (Sport, Health and Exercise) at a UK university took part in the survey. The survey assessed student engagement through the University Student Engagement Inventory (USEI) and assessment preferences using the Assessment Preference Inventory (API). Our results indicate no significant differences in student engagement across different ethnic groups. However, notable distinctions were observed in assessment preferences. White students preferred to receive more detailed remarks in their feedback than Asian and Black students. All participants ranked oral presentations as their least preferred assessment type. On the other hand, preferences for the most favoured assessment type varied by ethnicity; White students preferred multiple-choice question exams, while Asian and Black students preferred coursework essays. These findings suggest that, while engagement levels may be similar across ethnic groups, preferences for feedback and assessment types differ, which can help educators develop more inclusive and effective assessment strategies.